PENGARUH MOTIVASI WIRAUSAHA, KEMANDIRIAN PRIBADI, DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA DI SENTRAL WISATA KULINER BRATANG BINANGUN SURABAYA - Kartika Putri Ardani; Sri Andayani; Diana Juni Mulyati (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2024)
Currently, the Surabaya city government has provided spaces for micro, small, and medium enterprises (UMKM) or street vendors to sell their products. With the establishment of a central culinary tourism area by the government, it is expected to help the local community, especially the people of Surabaya. Research has been conducted to identify potential problems, such as the influence of entrepreneurial motivation, personal independence, and entrepreneurial knowledge on business success. Unequal competition contributes to uneven business success among the vendors. The lack of entrepreneurial motivation, personal independence, and supported entrepreneurial knowledge can lead to unequal business success in the culinary tourism center of Bratang Binangun, Surabaya.This study utilized a quantitative research method and employed a census method. A questionnaire was distributed to the vendors as the research instrument. The sample size consisted of 32 respondents, determined through a census method. Data analysis was performed using the Independent Sample Test. The research findings indicate a significant influence (0.000 < 0.05) of entrepreneurial motivation, personal independence, and entrepreneurial knowledge on business success in the culinary tourism center of Bratang Binangun, Surabaya.